2006
DOI: 10.1111/j.1532-5415.2006.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

An Emergency Medical Services Program to Promote the Health of Older Adults

Abstract: EMS screening of older adults during emergency responses is feasible, but a simple intervention of providing educational materials to patients during emergency responses and faxing notifications to physicians appears insufficient to address patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 25 publications
0
98
0
Order By: Relevance
“…Although no risk screening tools appear to be used by EMS, one study described how EMS services have attempted to provide more extensive care through screening, education, and referral programs for older patients in an attempt to identify unmet health care needs (Table 2). (21) EMS-based public health promotion programs are rare; however, Shah et al (21) determined that it is feasible for EMS agencies to take on non-traditional roles in public health. In addition, an EMS specific tool is currently in the derivation phase (PERIL -Paramedics Assessing Elders at Risk For Independence Loss).…”
Section: Frailty In Ems Patientsmentioning
confidence: 99%
“…Although no risk screening tools appear to be used by EMS, one study described how EMS services have attempted to provide more extensive care through screening, education, and referral programs for older patients in an attempt to identify unmet health care needs (Table 2). (21) EMS-based public health promotion programs are rare; however, Shah et al (21) determined that it is feasible for EMS agencies to take on non-traditional roles in public health. In addition, an EMS specific tool is currently in the derivation phase (PERIL -Paramedics Assessing Elders at Risk For Independence Loss).…”
Section: Frailty In Ems Patientsmentioning
confidence: 99%
“…Our review of titles and abstracts suggested that 138 articles might be eligible. After studying full texts, we confirmed that 13 papers 61,62,66,80,[89][90][91][92][93][94][95][96][97] reporting 12 studies met our inclusion criteria, as detailed in Figure 1. Table 4 summarises the 12 included studies; Tables 5 and 6 describe them in more detail and Table 7 assesses their quality.…”
Section: Inclusionmentioning
confidence: 56%
“…Of the 12 studies, six 61,62,66,80,89,94 came from the UK, four [90][91][92][93] came from the USA, one 97 came from Australia and one 95 came from New Zealand. Study designs comprised two RCTs 61,66 (one of which 61 published a separate paper evaluating cost-effectiveness element of the study), 62 nine cohort studies (of which six did not include a comparator arm 89,[91][92][93]95,97 and three included intervention and control arms 80,90,96 ) and one qualitative study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations